Real Time Motion Detection Video Surveillance For Categorizing Between Human and Non-Human - Jain, Meghna; Agarwal, Kriti; Sheth, Vrajesh; (Mohite), ,Vaishali Gaikwad (IJRDO -Journal of Computer Science Engineering, 2015)
An Automated Video Surveillance and monitoring system has a rich history. Traditional video surveillance systems are large in number but still retrenched in an extensive manner. The system targets at tracking an object and segregates it as Human or Non-Human entities, wherein the non-human entities would be further analysed into its respective categories which would help in subsequent analytics.The system when recognizes suspicious activity, it is captured instantly and the alarm is triggered for the security purpose. It is necessary to introduce an application that automatically formulates the images captured in order to detect precarious situations or undesirable encroached objects. Object detection is a mandatory step in automated video surveillance. Foreground extraction in harmony with background subtraction is further collaborated with the thresholded image for revelation of entities. The system engages a contemporary combination of Background Modelling, Support vector machine (SVM) and a Human Detection for Surveillance (HDS) System. The HDS system assimilates a Histogram of Oriented Gradients based on a human detector which is in limelight for its performance in detecting humanistic appearances. Detailed analysis is carried out on the performance of the system on various test videos.